Diverse expression of selected SMN complex proteins in humans with sporadic amyotrophic lateral sclerosis and in a transgenic rat model of familial form of the disease. - Janina Rafałowska; Dorota Sulejczak; Stanisław J Chrapusta; Roman Gadamski; Dorota Dziewulska (PLoS ONE, 2014)
BACKGROUND AND OBJECTIVE:There is circumstantial evidence linking sporadic amyotrophic lateral sclerosis (ALS) cases to a malfunction or deficit of a multimeric SMN complex that scrutinizes cellular RNAs; the core of this complex is survival motor neuron (SMN, or gemin 1) protein. We intended to verify this hypothesis by comparing the expression of both SMN and several other functionally associated gemins in the anterior horn motoneurons of patients who died of sporadic ALS (sALS), of transgenic rats with overexpression of the mutated human superoxide dismutase 1 gene (SOD1(G93A)) that represent a model of familial ALS (fALS), and of the respective controls. METHODS:Using archival material of paraffin blocks with samples of human and rat spinal cords, immunohistochemical reactions with antibodies against SMN and gemins 2, 3, and 4 were performed and assessed by light microscopy. RESULTS:The expression of SMN and all other studied gemins was observed in motoneurons of sALS patients, fALS rats, and in all controls, although the intensity varied. The immunolabeling was most intense in sALS patients with relatively fast disease course, and decreased with increasing disease duration in both the human sALS and rat fALS material. Irrespective of the disease stage, sALS material showed no or very low gemin 2 immunoreactivity, while clear gemin 2 immunoreactivity was observed in all fALS rats and control material. CONCLUSION:The deficient expression of gemin 2 in spinal cord motoneurons in human sALS may lead to a dysfunction and loss of neuroprotective action of the SMN complex.